Penerapan Health and Safety Regulations dari Karyawan Gerai D’crepes di Salah Satu Mall di Bali - Wibowo, Cindy Lorensia; Kusno, Kelly; I Gusti Ayu Melistyari Dewi (PT. Hafasy Dwi Nawasena, 2023)
The Implementation of Health and Safety Regulation of employees in working will impact to the quality of the food. Hence, socialization and evaluation related to Health and Safety Regulation towards employees are needed. The purpose of this research is to know The Implementation of Health and Safety Regulations of D’Crepes ’s Employees In One Of The Mall In Bali. This studies used descriptive qualitative method. Data collecting using observation method, documentation, and interview. The subject of this research were D’Crepe ‘s employees in one of the mall in Bali with 3 employees. Data analysis used descriptive analysis then presented through table and percentage. The results showed that the implementation of health and safety in D’crepe was quite good, the employees obey the grooming SOP which are wearing cap, hand gloves, face mask, and shoes. They also obey the cleaning schedule well. Unfortunately, there are only one sink provided, more sink is needed for huge production, cleanliness while rush hour were ignored where the storage were left opened and toppings are exposed, production area were also messy.